Experience in Partial Discharge Investigation of a 155 MVA Air-Cooled Generator - Pathanrat, Khomsan; Chumpiboon, Komin; Jeenmuang, Siwakorn; Worthong, Tehneht; Pannil, Pittaya; Pattanadech, Norasage (My University, 2024)
This paper presents the Partial Discharge (PD) and Polarization and Depolarization Current (PDC) investigation for a 155 MVA air-cooled generator. The visual inspection of the stator winding insulation was carried out during the annual preventive maintenance. Several defects in the area of the end winding stator were evidenced. Thereafter, the refurbishment of these problems was performed to improve the stator winding insulation condition, and the offline PD & PDC test was conducted accordingly. Besides, the online PD was continuously monitored, through capacitive PD sensors which have been installed on the terminal of the generator two units per phase. The operating conditions during online PD measurement were also recorded. In this paper, the results from both offline and online PD measurements were presented.
Keywords: Generator; Partial discharge (PD); Polarization and depolarization current (PDC); Stator Winding Tnsulation